The paths to inclusive education: the relationship between guiding documents and the inclusion process (Research, Society and Development, 2020)
The present study seeks to identify the educational actions planned about inclusive education, through the analysis of the guiding documents of a school in the municipal education network of a municipality on the western border of Rio Grande do Sul, as well as through the perceptions of the pedagogical coordinator of the school. This is a qualitative study, characterized as the objectives as a descriptive research. The data collection procedure took place through the analysis of the Pedagogical Political Project (PPP) and the School Regiment, as well as a semi-structured interview with the school's pedagogical coordinator. The data were organized and presented through a descriptive analysis. The research scenario is a municipal public school, with 1290 students enrolled in 2018, 53 of which have some global developmental disabilities and/or disabilities. Regarding the results found, the PPP and the School Regiment address some items that plan specific strategies for school inclusion, however, they still lack a specific proposal that addresses students with disabilities, global developmental disorders and/or high skills /giftedness. Thus, it is suggested that some items of the PPP and the School Regiment may be reformulated to address the specificities related to school inclusion. In addition to the investment in continuing education in this perspective for teachers and other professionals involved.